Epidemiology and Diagnosis of Human Leptospirosis in Malaysia - Mohamed El-Jalii, Isam Mohamed Ali (2000)
Retrospective study of human leptospirosis in Malaysia based on microscopic agglutination test (MAT) showed 13% overall prevalence of infection for the period 1983-1998. Results indicated that the prevalence was decreasing in the last five years (1994-1998). The prevalence was highest among Indians (16.67%) followed by Malays (11.48%) and the least among Chinese (5.88%). The 20-29 year-old group showed the highest prevalence of infection (17.13%). Less than 10 year-old group showed the least prevalence of infection (5.66%). Generally, many of the cases occurred between the ages of 20-50 years. Serological survey based on enzymelinked immunosorbent assay (ELISA) showed a high overall prevalence (12.56%) of leptospiral infection. Kuala Lumpur showed the highest prevalence (19%) whilst Penang recorded the lowest prevalence (6.67%). No significant differences in the prevalence between the other states was noted A comparative study of three serological tests, namely enzyme-linked immunosorbent assay (ELISA), microscopic agglutination test (MAT) and indirect hemagglutination (IHA), test was carried out to evaluate these tests in the diagnosis of human leptospirosis. A total of 3000 serum samples from three groups of people were examined. In Group I, IgM and IgG-ELISA were able to detect a number of cases in the first sampling before MAT titres were detectable. In the second sampling, all samples positive for MAT were also positive for IgM-ELISA. IHA test gave positive reactions with only 38% of the samples while all samples were positive for ELISA. In Group II, ELISA detected IgM and IgG to leptospires in the samples which were negative to MAT. These were samples from patients with clinical signs of leptospirosis. The polymerase chain reaction (peR) was evaluated as a tool for diagnosis of leptospirosis and differentiation of leptospiral strains. Urine samples with as little as 10 serovar hardjo cells per ml of urine were positive on peR indicating high sensitivity of the test. Detection of small number of leptospiral cells in urine by peR was an advantage over culture. Random amplification polymorphic DNA (RAPD) fingerprinting was applied to differentiate leptospiral strains. Two primers were tested for their abilities to generate individual RAPD fingerprints. The DNA profiles obtained with each primer were distinct and reproducible. The fingerprint obtained could be useful for distinguishing the serovars up to the strain level. Profiles obtained revealed genetic heterogeneity between serovars belong to one serogroup.Analysis of leptospiral DNA with restriction enzymes, Hind III, BamH I and EeoR I revealed a high heterogeneity between the serovars examined. This high heterogeneity may be due to the large genome of the genus Leptospira. No relationship was found between the restriction patterns and the species from which the isolate was isolated. Similarities were observed among isolates of the same serovar. The 1 0 leptospiral field isolates were assayed for presence of plasmid DNA. Only two isolates were found to harbour plasmid DNA. The plasmid profiling obtained is of limited epidemiological value for differentiation of leptospiral isolates. It appears that human leptospirosis is an endemic infection in Malaysia. The findings showed that ELISA was a suitable serological test for diagnosis of leptospirosis compared to MAT and IRA tests. On the other hand, the application of peR and REA in the diagnosis of leptospirosis would be useful.